The impact of opioid analgesics with concomitant antipsychotic use on pain modulation and management in internal medicine: a cross-sequential study protocol - Grignoli, Nicola; Livoti, Simone; Greco, Angela; Pironi, Michela; Noseda, Roberta; Ceschi, Alessandro; Garo, Maria Luisa; Gabutti, Luca (Frontiers in Pain Research, 2025)
BackgroundAcute and chronic pain represents an escalating public health concern, necessitating safer and more effective in-hospital management approaches, including mental health. New treatment combinations involving psycholeptics are rising, but real-world evidence is lacking.ObjectivesThe study's primary objective is to evaluate the impact of combined opioid analgesics and antipsychotics in-hospital medication on pain modulation. The secondary objective is to evaluate pain management.MethodsThe cross-sequential study designed by this protocol will analyze retrospective data on 5,000 hospital admissions over four years (2019–2023) gathered from Electronic Health Records (EHR) of a multisite hospital in southern Switzerland. Eligible patients are aged 18 or older and hospitalized in an Internal Medicine ward. All patients with documented pain intensity assessment through a Visual Analogue Scale (VAS ≥ 1) will be included. Cross-sectional data on demographic and clinical variables and type of medication (opioid analgesics, antipsychotics, and selected other drugs according to the Anatomical Therapeutic Chemical classification system) will be screened at hospital admission (T1) and discharge (T2). Pain modulation will be assessed by gravity (VAS mean), intensity (VAS peak/extreme value), and pain treatment effectiveness (ΔT2-T1 VAS). Hospitalization paths (short- and long-term readmissions and total length of hospital stays) will be scrutinized as additional longitudinal indices for pain management and excluded from the cross-sectional analysis. A mixed model approach will assess VAS changes from T1 to T2. Logistic regression and regression models for count data will be used for short- and long-term readmission, respectively. Propensity score matching will be used to mitigate selection bias.DiscussionThis methodological approach combines cross-sectional and longitudinal EHR data gathering in a cross-sequential design. This integration allows for a comprehensive examination of pain modulation and management among internal medicine recipients of concomitant opioids and antipsychotic treatment, spanning both hospitalization and post-discharge periods. By leveraging EHR data, the study protocol ensures reliability and standardization while minimizing missing information. Additionally, the protocol addresses the potential limitations of observational designs.ConclusionsThis method offers a comprehensive and rigorous approach to investigating pain modulation and management in internal medicine patients receiving combined opioid analgesics and antipsychotics, with potential implications for enhancing clinical practice and healthcare resource utilization.